Gabbroic Rocks in Mawat Ophiolite Complex, NE Iraq: Geochemical Constraints on their Tectonogenesis - Al-Jboury, Mohammed A.; Al-Taweel, Omar S. (Iraqi Journal of Science, 2022)
The Mawat Ophiolite Complex located in north-eastern Iraq represents part of the Iraqi Zagros Suture Zone, located at the border between the Arabian-Iranian plates. It consists of peridotite, gabbro, subvolcanic sheeted dykes and volcanic pillow lava. The geochemical signatures of the gabbro show a significant variation in major elements concentration, low concentrations of TiO2 (0.06-0.36 wt.%), Na2O (0.44-0.98 wt.%), K2O (0.024-0.48 wt.%), P2O5 (0.002-0.009 wt.%) and moderate variations in SiO2 (46.13-53.77 wt.%) with wide ranges and high concentration of Al2O3 (13.87-22.18 wt.%), Fe2O3 (0.04-2.95 wt.%), FeO (2.68-8.76 wt.%), MgO (8.09-14.28 wt.%) and CaO (11.08-17.04 wt.%). The flat REE patterns of the present rocks represent island arc tholeiite (IAT) tectonics and a subduction-related environment. The main features of the magma generated in the supra subduction zone are the enrichment of LILEs and depletion of the HFSEs and the strong negative Nb anomaly. Geochemical evidence indicates that the tholeiitic gabbros were generated in an arc-related tectonic setting. The tectonomagmatic diagrams for gabbros and the very low Ti content propose that the gabbroic rocks of Mawat Ophiolite have island arc tholeiitic (IAT) and possibly boninitic affinities which have a related to the supra-subduction zone (SSZ).